Spinal Bone Lymphoma with Intraspinal Extension: Case Report - Vargas-Urbina, John (2024)
Introduction: Spinal bone lymphoma is a rare disease, with diffuse large B-cell lymphoma being the most common subtype. It is usually a late manifestation of a systemic disease. Its management is multidisciplinary, including surgery, chemotherapy and radiotherapy. Clinical case: A 40-year-old woman, with human immunodeficiency virus infection, miliary tuberculosis monoresistant isoniazid, with disease period of 7 month with progressive motor and sensory deficit in addition to sphincter dysfunction. The contrasted MRI shows a left vertebral and paravertebral tumor that invades spinal canal through left T2/T3 foramina with spinal cord compression. Laminectomy T2 and T3 plus total resection of tumor plus spinal fixation is performed. The patient progressively recovered the motor deficit and began chemotherapy with a good response. Conclusion: The spinal bone lymphoma is an infrequent etiology of bone tumor of the spine, which requires multidisciplinary management.